Pengaruh Kualitas Layanan dan Harga terhadap Loyalitas Pelanggan Rumah Makan Prambanan di Samarinda - Wasti Amat; Suharno Suharno; Sri Wahyuni (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This study, entitled The Effect of Service Quality and Price on Customer Loyalty Eating Prambanan In Samarinda.This aim of the research is to determine the influence of Quality of Service and Price on Customer Loyalty Eating Prambanan in Samarinda. Research was conducted on Eating Prambanan.The sampling technique in this research was Purpositive Sample is where this technique requires the researchers to apply some members of the sample requirements and only those who qualify are allowed chosen in the sample with a sample size of 50 respondents. The data in this study uses primary data is interview and questionnaire. Hypothesis test used in this study is Multiple Linear Regression using SPSS version 20. The results showed that: 1) Effect of Service Quality variable proved significant effect on Customer Loyalty, 2) variable declared price has a significant impact on the Customer Loyalty.